Green Finance and Competitiveness in Fintech Adoption: Digital Transformation and Sustainability in Indonesian Banks - Rachmawati, Windasari; Sugeng Wahyudi; Wisnu Mawardi (Universitas Muhammadiyah Surakarta, 2025)
The increasing global focus on sustainability is prompting organizations to integrate financial technology (Fintech) solutions to increase their sustainability outcomes. This research seeks to explore the intermediary role of green finance and competitiveness, along by the moderating influence of digital transformation (DT), on the link among Fintech and sustainability performance. The study constructs a conceptual framework based on responses from bank employees in Central Java, Indonesia. Data were gathered from 170 bank employees and analyzed utilizing Smart-Partial Least Square (PLS). The findings reveal that Fintech adoption does not significantly negatively impact sustainability performance. Additionally, while Fintech adoption shows a positive but insignificant effect on green finance and competitiveness, it has an insignificant negative impact on competitiveness and sustainable performance. Digital transformation, as a moderator of the connection among Fintech adoption and green finance, competitiveness, and sustainability performance, also shows an insignificant positive effect.